THE ROLE OF RSV VACCINATION IN THE PREVENTION OF RESPIRATORY DISEASES IN OLDER ADULTS - Karaś, Katarzyn; Mroszczyk, Sylwia; Nowicki, Dawid; Muszyńska, Małgorzata; Małyszczak, Paulina (International Journal of Innovative Technologies in Social Science, 2026)
Introduction and objective: Respiratory syncytial virus (RSV) is one of the leading causes of lower respiratory tract infections in older adults. In 2023, the first subunit vaccines based on the prefusion conformation of the RSV fusion protein - Arexvy and Abrysvo - were approved, followed in 2024 by the mRNA-1345 vaccine marketed as mRESVIA. The aim of this study is to present the importance of RSV vaccination in the prevention of respiratory diseases in adults aged ≥60 years.Review methods: The literature review was conducted using articles available in the PubMed, EMBASE, Web of Science, and Cochrane Library databases. The analysis focused on studies addressing RSV epidemiology as well as the efficacy and safety of RSV vaccines, particularly Arexvy and Abrysvo. FDA and CDC/ACIP documents were also included. Studies involving pediatric populations and narrative reviews were excluded.State of knowledge: RSV accounts for 5-10% of lower respiratory tract infections in older adults, with mortality among infected individuals reaching 2-5%. Arexvy induces a strong immune response, while Abrysvo is characterized by a favorable safety profile. Studies have demonstrated vaccine efficacy ranging from 66-83% against RSV-associated lower respiratory tract disease and over 90% against severe RSV infection. Protection conferred by Arexvy persists for at least two seasons.Summary: RSV vaccination reduces the incidence of lower respiratory tract infections, hospitalizations, and mortality in the older adult population. The 2024 ACIP guidelines recommend a single dose of RSV vaccine for individuals aged ≥75 years and for adults aged 60-74 years with risk factors, without routine booster doses.